Placental Inflammation in Preterm Premature Rupture of Membranes and Risk of Neurodevelopmental Disorders - Elizabeth Marie Cervantes; Sylvie Girard (Cells)
Preterm premature rupture of membranes (pPROM) is a leading cause of preterm birth (PTB) and is increasingly recognized for its association with neurodevelopmental disorders (NDDs). The disruption of fetal membrane integrity introduces potential infection and inflammation into the intrauterine environment, triggering immune responses that may affect fetal development. Placental inflammation plays a pivotal role in mediating these effects, exposing the fetus to cytokines, oxidative stress, and potential microbial insults that contribute to adverse neurodevelopmental outcomes. This review examines the current evidence of the mechanistic pathways linking pPROM-induced placental inflammation to NDDs, emphasizing the roles of pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) in the inflammatory responses. We discuss how these immune activations lead to immune cell recruitment and excessive (or uncontrolled) production of inflammatory mediators, leading to an overall inflammatory imbalance that has been linked to disrupted fetal brain development in animal models. Animal models provide critical insights into how both sterile and pathogenic placental inflammation alter fetal neurodevelopment, while human studies, though limited, highlight promising biomarkers and potential therapeutic targets. This review identifies critical knowledge gaps and outlines future directions to mitigate the impact of placental inflammation on long-term infant health.